Infection Prevention and Control Capacity Building During 2018–2019 Democratic Republic of Congo Ebola Virus Disease Outbreak. (October 2020) - Baller, April; Ousman, Kevin; Padoveze, Maria Clara; Basilubo, Charles; Bobwa, Rodrigue; Engrand, Antoine; Houndjo, Bienvenu; Cihambanya, Landry; Lotemo, Jonathan; Mangala, Samuel; Mirindi, Patrick; Tatabod, Jude; et al.
Abstract : Background: As of July 1, 2019, 18% of all cases in the Ebola virus disease (EVD) outbreak in the Democratic Republic of Congo (DRC) were healthcare-associated (ie, nosocomial) infections (HAIs) and healthcare worker (HCW) infections. Although progress has been achieved, gaps remained in infection prevention and control (IPC), specifically, a need to reinforce standardized, evidence-based IPC practices to effectively address HAIs. The Ministry of Health (MOH), in collaboration with partners, developed an IPC tool kit consisting of >70 documents (ie, terms of reference, standard operating procedures, training modules, etc) to improve HCW IPC knowledge and practices at healthcare facilities among staff. The tool kit incorporated international IPC standards, DRC-specific experiences, and best practices. Thus, it serves as a technical and operational package, covering general guidance (standard precautions) and EVD specific issues. Methods: A decentralized rollout approach was used to disseminate the tool kit content at the various health-system levels over several months. Initially, national-level training of trainers was held, followed by subnational-level training of IPC supervisors and key IPC implementers, and lastly, training of healthcare facility (HCF) IPC focal persons. The 5-day training adhered to the MOH standard of 60% theory and 40% practice. Participants completed evaluations before and after training; changes in knowledge between the pre- and posttraining tests were analyzed and the results of the statistical tests were reported ( P < .05 was considered statistically significant). Results: In total, 294 IPC supervisors were trained across 7 subnational commissions. Data were analyzed for 138 participants. Participants were 60.9% IPC supervisors, 8% WASH supervisors, and 31% others. MOH representation was 52.9% The average results before the test were 66% (19.8 of 30), the average posttest results were 72% (21.6 of 30)—a significant improvement. The worst-performing pretest IPC domain was IPC approach, and facility closure was the worst performing for posttest. As of November 11, 15.7% of all cases were HAIs. Conclusions: The IPC training program initiated during an outbreak can increase knowledge and potentially improve practices and confidence. An association with the downward HAI trend is yet to be validated. The MOH anticipates that this tool kit will be the go-to resource for future Ebola outbreaks and that it will be incorporated into the preservice medical curriculum to ensure a resilient heath system. Funding: None Disclosures: None